Synthesis and evaluation of quinoline-derived antibiotics - Darien Allen (UNC Test Journal, 2025)
The medical field has countless issues that make it difficult to treat patients effectively, and the underlying one is antibiotic resistance. Antibiotic resistance came to be through the periodical evolution of bacteria after treatment, it makes the methods and antibiotics used to kill certain infectious bacteria less and less effective. In this work, we discuss the creation of new antibiotics and the making of new substituents for old antibiotics to make them more effective. We synthesize new molecules that resemble old antibiotics and have the capability to target and inhibit the ATP synthases of gram-negative bacteria like P. aeruginosa and A. baumannii. We have found that it is best to have primary and positive amines, as well as high overall charges. With this information, I plan to create a new quinolone base through a Vilsmeier-Haack reaction. To create new pathways to analogs capable of both permeating and avoiding efflux. This new quinolone base will undergo various steps in a reaction process to create a breath of fresh air in the field of antibiotic synthesis.